2010
DOI: 10.1016/j.actbio.2009.12.052
|View full text |Cite
|
Sign up to set email alerts
|

Functional biomimetic analogs help remineralize apatite-depleted demineralized resin-infiltrated dentin via a bottom–up approach

Abstract: Natural biominerals are formed through metastable amorphous precursor phases via a bottom-up, nanoparticle-mediated mineralization mechanism. Using an acid-etched human dentin model to create a layer of completely-demineralized collagen matrix, a bio-inspired mineralization scheme has been developed based on the use of dual biomimetic analogs. These analogs help to sequester fluidic amorphous calcium phosphate nanoprecursors and function as templates for guiding homogeneous apatite nucleation within the collag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 60 publications
2
95
0
4
Order By: Relevance
“…Reducing application time by the use of a simplified absolute ethanol replacement protocol may result in the collapse of the demineralized collagen matrix, either by evaporation of water or absolute ethanol, when the procedure of ethanol-water replacement is not meticulously followed. Nevertheless, the principles of removal of free and loosely bound water from the intrafibrillar compartments of the collagen matrix behind this philosophical bonding regime have brought to fruition a resin-dentin interfacial remineralization scheme (Tay and Pashley, 2009;Kim et al, 2010a) that is based on a similar principle of progressive water replacement (Magne et al, 2001) by intrafibrillar remineralization of collagen fibrils with apatite nanocrystals generated via the use of biomimetic analogs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reducing application time by the use of a simplified absolute ethanol replacement protocol may result in the collapse of the demineralized collagen matrix, either by evaporation of water or absolute ethanol, when the procedure of ethanol-water replacement is not meticulously followed. Nevertheless, the principles of removal of free and loosely bound water from the intrafibrillar compartments of the collagen matrix behind this philosophical bonding regime have brought to fruition a resin-dentin interfacial remineralization scheme (Tay and Pashley, 2009;Kim et al, 2010a) that is based on a similar principle of progressive water replacement (Magne et al, 2001) by intrafibrillar remineralization of collagen fibrils with apatite nanocrystals generated via the use of biomimetic analogs.…”
Section: Discussionmentioning
confidence: 99%
“…Nanoleakage studies have identified water-filled channels within hybrid layers, indicating that not all residual water is removed (Tay and Pashley, 2003). Recent studies that demonstrated intrafibrillar remineralization of collagen fibrils within hybrid layers further imply that contemporary dentin adhesives cannot replace free and loosely bound water from the intrafibrillar spaces, even when resin monomers are able to encapsulate the collagen fibrils (Tay and Pashley, 2009;Kim et al, 2010a). Water sorption also plasticizes hydrophilic adhesives and lowers their mechanical properties (Ito et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This fact makes the non-monomer-infiltrated collagen at the bottom of the hybrid layer more prone to degradation by proteolytic enzymes, as dentinal matrix metalloproteinases and, consequently, the resin-dentin bonding interface could be compromised [2]. The incorporation of bioactive materials has been proposed, attempting to backfill the denuded collagen to prevent hybrid layer deterioration [8][9][10][11]. Calcium silicates and calcium orthophosphates have already been experimentally tested on adhesives aiming at this therapeutic/remineralization effect [28,29].…”
Section: Resultsmentioning
confidence: 99%
“…In order to surpass this problem, one option would be to develop an adhesive system that would induce the release of ions with the goal of filling this exposed collagen fiber region with mineral formation [7][8][9][10][11]. Niobium pentoxide (Nb 2 O 5 ) has shown mineralization induction through mineral deposition in previous studies [12][13][14], demonstrating promising proprieties.…”
Section: Introductionmentioning
confidence: 99%
“…The use of dual biomimetic analogs such as a combination of polycarboxylic acid and polyphosphate to induce hierarchical intrafibrillar mineralization has been further demonstrated in a single-layer reconstituted collagen model (Liu et al, 2011a,b). This biomimetic mineralization strategy has been adopted to remineralize resinsparse, water-rich zones within hybrid layers created by etch-and-rinse adhesives, to "back-fill" bonding defects via intrafibrillar remineralization of denuded collagen fibrils within the hybrid layer (Tay and Pashley, 2009;Kim J et al, 2010) for increasing the durability of resin-dentin bonds (Kim YK et al, 2010a;Liu et al, 2011c).…”
Section: Introduction Cmentioning
confidence: 99%